Uso de plantas medicinais nas comunidades quilombolas de Coremas, Paraíba-PB, Brasil - Pellegrino, Noêmia Suely Lacerda (2015)
Traditional communities are considered in possession of great knowledge on plant diversity and have accumulated over time much knowledge about the environment in which they operate. Ethnobotany comes this way, study the knowledge that traditional communities have on plants, which are of great importance to these communities, either as fuel, ornamentation, in control, relief or cure of common everyday ailments. When it comes to medicinal plants, the use and knowledge of these species are directly related to maintaining the health and survival of a community. This study aimed to carry out ethnobotanical survey on knowledge and use of medicinal plants by the residents of two maroon communities in the municipality of Coremas, Paraíba, being structured in a chapter shaped article. The article aims to survey the species with medicinal potential according to local knowledge using two analyzes, the Value in Use and Informant Consensus Factor, in addition, makes a comparison between men and women in relation to knowledge about medicinal plants . It was applied informal interviews and semi-structured questionnaires, with a total of 72 families interviewed in both communities, 72 women and 54 men between 22 and 81 years old. A total of 17 species in 14 plant families have been identified. It has been known from the interviews that the most used plants are herbs and leaves are preferably used in the preparation mainly teas. Most species are cultivated in gardens and yards, reinforcing the idea that these communities is closely related to the local flora.